Membangun Budaya Disiplin Berbasis Motivasi Di Lingkungan Kerja - Defi Warman (Eko dan Bisnis: Riau Economic and Business Review, 2025)
The purpose of this study was to determine the effect of motivation on employee work discipline. To achieve this goal, a study was conducted using a sample of 47 people, using a simple random method (accidental random sampling). The data analysis method used simple linear regression. Based on the results of testing motivation has a significant effect on employee work discipline at .   Pekanbaru, this is proven based on the t-test found that t-count is greater than t-table (9.913 > 2.014). The value of R. Square (R2) of 0.686 (68.6%) explains that the motivation variable contributes to work discipline by 68.1%. While the remaining 31.4% describes other independent variables that were not observed in this study. Recommendations that can be submitted It is hoped that the company can pay attention to employees so that they quickly adjust to the work environment because this statement gets the lowest response from respondents.